2017
DOI: 10.1589/jpts.29.1788
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive change impairs balance control in older patients with low back pain

Abstract: Abstract. [Purpose] This study aims to determine the specific proprioceptive control strategy used during postural balance in older patients with low back pain (LBP) and non-LBP (NLBP) and to assess whether this strategy is related to proprioceptive decline and LBP. [Subjects and Methods] Pressure displacement center was determined in 47 older persons with LBP and 64 older persons with NLBP during upright stance on a balance board without vision. Gastrocnemius (GS) and lumbar multifidus muscle (LM) vibratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…Furthermore, they reported that poor proprioception could lead to impaired sensory control of the limbs during periods of movement and when there is increased dynamic joint load. Previous studies have shown that elderly patients with LBP depend on proprioceptive inputs of the Vater-Pacini corpuscles [5,17], which may imply that the postural strategy adopted by elderly adults with lumbar spondylosis depends on the mechanoreceptors of the Vater-Pacini corpuscles in the LM and GS muscles. Other studies reported that proprioception and muscle spindles in the trunk decrease in both young and elderly adults with LBP [6][7][8][9][10]15,16,[19][20][21].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, they reported that poor proprioception could lead to impaired sensory control of the limbs during periods of movement and when there is increased dynamic joint load. Previous studies have shown that elderly patients with LBP depend on proprioceptive inputs of the Vater-Pacini corpuscles [5,17], which may imply that the postural strategy adopted by elderly adults with lumbar spondylosis depends on the mechanoreceptors of the Vater-Pacini corpuscles in the LM and GS muscles. Other studies reported that proprioception and muscle spindles in the trunk decrease in both young and elderly adults with LBP [6][7][8][9][10]15,16,[19][20][21].…”
Section: Discussionmentioning
confidence: 98%
“…COP excursion was recorded using a balance board (Wii; Nintendo Co., Ltd., Kyoto, Japan) [5,[16][17][18][23][24][25]. Balance board data were acquired using a sampling frequency of 100 Hz and calculated using MATLAB (MathWorks, Inc., Natick, MA, USA).…”
Section: Muscle Vibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the title andabstract screening, 35 fulltext articles were retrieved. The full-text review was completed to determine nal inclusion; 17 articles (13 case-control studies [20][21][22][23][24][25][26][27][28][29][30][31][32] , four RCTs [33][34][35][36] ) met the inclusion criteria. Only the 13 case-control studies were included in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%